2005
DOI: 10.1002/hed.20149
|View full text |Cite
|
Sign up to set email alerts
|

Primary mucosa-associated lymphoid tissue (MALT) lymphoma of the larynx

Abstract: We may assume that chronic laryngitis could be a precursor to MALT lymphoma. This case is the first one to our knowledge of a primary MALT lymphoma of the larynx treated with conservative management combining surgical excision, reflux therapy, and eradication of gastric H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…4 Although 90% of tumors involving the larynx are squamous cell carcinoma, 5 laryngeal lymphoma is an important differential consideration because lymphoma is treated with chemoradiation instead of surgery. [1][2][6][7][8][9] Early detection of lymphoma allows improved patient care and may result in decreased dissemination of the disease process. 10,11 The purpose of this study was to identify imaging features of laryngeal lymphoma that could differentiate it from the far more common squamous cell carcinoma of the larynx and thus aid in the early detection of this rare tumor and lead to its proper treatment.…”
mentioning
confidence: 99%
“…4 Although 90% of tumors involving the larynx are squamous cell carcinoma, 5 laryngeal lymphoma is an important differential consideration because lymphoma is treated with chemoradiation instead of surgery. [1][2][6][7][8][9] Early detection of lymphoma allows improved patient care and may result in decreased dissemination of the disease process. 10,11 The purpose of this study was to identify imaging features of laryngeal lymphoma that could differentiate it from the far more common squamous cell carcinoma of the larynx and thus aid in the early detection of this rare tumor and lead to its proper treatment.…”
mentioning
confidence: 99%
“…3 Kania et al reported MALT laryngeal lymphomas to be treated primarily by surgical excision. 33 Flow cytometry and karyotypic analysis accurately helps in diagnosis and subclassification of lymphomas as well as in the determination of prognostic indicators by extensive cellular phenotypic characterization of the tumor specimen. 3 This helps the oncosurgeons in creating patient-specific treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…184,185 Individual case reports have described patients with Sjögren's syndrome, 186 rheumatoid arthritis, 187 or chronic laryngitis secondary to extraesophageal reflux with Helicobacter pylori gastritis. 188 In rare cases patients are HIV positive 97,183 or have another underlying immunodeficiency. 189 Patients present with hoarseness, dyspnea, progressive or acute airway obstruction, sore throat, foreign body sensation, or dysphagia.…”
Section: Differential Diagnosis Of Hodgkin's Lymphoma Of the Thyroidmentioning
confidence: 99%
“…37,97,181,184,185 The tumors usually are smooth surfaced, submucosal, raised, often polypoid lesions. 183,184,188,190 Circumferential involvement of the larynx is also described. 186 Pedunculated tumors may prolapse into the airway.…”
Section: Differential Diagnosis Of Hodgkin's Lymphoma Of the Thyroidmentioning
confidence: 99%
See 1 more Smart Citation